2016
DOI: 10.1515/jccm-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Anti-platelet Therapy Resistance – Concept, Mechanisms and Platelet Function Tests in Intensive Care Facilities

Abstract: It is well known that critically ill patients require special attention and additional consideration during their treatment and management. The multiple systems and organ dysfunctions, typical of the critical patient, often results in different patterns of enteral absorption in these patients. Anti-platelet drugs are the cornerstone in treating patients with coronary and cerebrovascular disease. Dual anti-platelet therapy with aspirin and clopidogrel is the treatment of choice in patients undergoing elective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 85 publications
1
22
0
Order By: Relevance
“…The frequency of CYP2C19-reduced function genotypes (IM and PM) shows wide interethnic variation ranging from 20% to 65% in different populations. 15,16 In our population, the frequency of the genotypes mentioned earlier was 38.9%.…”
Section: Discussionsupporting
confidence: 44%
“…The frequency of CYP2C19-reduced function genotypes (IM and PM) shows wide interethnic variation ranging from 20% to 65% in different populations. 15,16 In our population, the frequency of the genotypes mentioned earlier was 38.9%.…”
Section: Discussionsupporting
confidence: 44%
“…A meta-analysis of 15 randomised controlled trials provided evidence that omega-3 PUFAs inhibited blood platelet aggregation [ 22 ]. Marine omega-3 PUFAs were also observed to overcome aspirin resistance (acetylsalicylic acid (ASA)) [ 28 , 55 ]. In studies on laboratory animals, it was demonstrated that ASA enhanced the antiplatelet effect of fish oil [ 56 ].…”
Section: Epidemiological Studies and Clinical Trialsmentioning
confidence: 99%
“…High percentage of individuals usually experiences antiplatelet therapy resistance that impairs successful prevention of cardiovascular events, and some determinants of resistance to antiplatelet therapy are gender responsive [141][142][143][144][145][146]. A prospective study on 160 patients with stable coronary heart disease (118 men and 42 women, aged 65:2 ± 7:8 years), indeed, showed a sex-related response to long-term double antiplatelet therapy (75 mg/day aspirin and clopidogrel for three months): female gender was more predisposed to resistance to both aspirin and clopidogrel compared to men [19].…”
Section: Dietary Factors Experimental Protocol Main Findings Refsmentioning
confidence: 99%